Prasa lokalna na konkurencyjnym rynku – założenia strategii rozwoju - Kowalczyk, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The author is of opinion that contemporary local press publications should focus on providing their readers with current information, whatever the distribution channel (print, the Internet, mobile news). This requires certain financial outlays, appropriate professional personnel, and the correct legal form to perform publishing activities and organize the publishing house efficiently. In the author’s opinion the current situation on the press publishing market requires a combination of traditional media with modern anderactive.